The Strengthening of Region Competitiveness by Implementing City Branding in Yogyakarta - Pasande, Mercy; Suhendra, Adi (Jurnal Bina Praja, 2017)
This study is about City Branding. This research is motivated by the potential of City Branding creation as a way to improve regional competitiveness. The purpose of this study is to describe the various efforts made by the local government of DIY to improve the competitiveness of the region with City Branding. This research uses the qualitative method. Data collection method is done by triangulation technique of data source. While data processing researcher does data reduction. The results obtained in this study are First, City Branding DIY has been running well. Rebranding DIY is likely to increase the competitiveness of regions, including local revenue. This is evidenced by the increase in investment achieved by the Government of Yogyakarta. It’s just that City Branding is still focused on tourism, but it can be used for other sectors. Second, the DIY rebranding (2014) provides many improvements, especially in terms of concept, logo, and tagline. In addition, the Yogyakarta provincial government has established city branding councils, city branding strategy roadmap and governor regulation of city branding in DIY. It’s just that there has been no evaluation since the rebranding was done by the provincial government of DIY, how this rebranding can be implemented by the local government and city branding council and there is no extent to which the strategy in the roadmap implemented.